Ask Question
23 January, 15:51

2b + 8 - 5B + 3 = - 13 + 8B - 5

+2
Answers (2)
  1. 23 January, 17:16
    0
    8b2-10b2+3=0

    Two solutions were found:

    b = ±√ 1.500 = ± 1.22474

    Step by step solution:

    Step 1:

    Equation at the end of step 1:

    ((8 • (b2)) - (2•5b2)) + 3 = 0

    Step 2:

    Equation at the end of step 2:

    (23b2 - (2•5b2)) + 3 = 0

    Step 3:

    Trying to factor as a Difference of Squares:

    3.1 Factoring: 3-2b2

    Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)

    Proof : (A+B) • (A-B) =

    A2 - AB + BA - B2 =

    A2 - AB + AB - B2 =

    A2 - B2

    Note : AB = BA is the commutative property of multiplication.

    Note : - AB + AB equals zero and is therefore eliminated from the expression.

    Check : 3 is not a square!

    Ruling : Binomial can not be factored as the

    difference of two perfect squares

    Equation at the end of step 3:

    3 - 2b2 = 0

    Step 4:

    Solving a Single Variable Equation:

    4.1 Solve : - 2b2+3 = 0

    Subtract 3 from both sides of the equation:

    -2b2 = - 3

    Multiply both sides of the equation by (-1) : 2b2 = 3

    Divide both sides of the equation by 2:

    b2 = 3/2 = 1.500

    When two things are equal, their square roots are equal. Taking the square root of the two sides of the equation we get:

    b = ± √ 3/2

    The equation has two real solutions

    These solutions are b = ±√ 1.500 = ± 1.22474

    Two solutions were found:

    b = ±√ 1.500 = ± 1.22474
  2. 23 January, 17:48
    0
    Answer: b=2.4

    Step-by-step explanation:

    First you want to add the same things on the same side: 2b + (-5b) which equals - 3b

    Then do the same thing to this:8+3=11

    Then:-13-5=-18

    Which shows as: 8-3b = - 18+8b

    Then you take the smallest subscript: - 3b and add itself to itself: - 3b+3b=0

    And do the same with the other subscript: 8b+3b=11b

    Which shows as: 8=-18+11b

    Then box the 11b and add the - 18 to itself: - 18+18=0

    Do the same with the other side: 8+18=26

    Which shows as: 26=11b

    Then divide each side by 11.

    Then this is your answer: b=2.4
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “2b + 8 - 5B + 3 = - 13 + 8B - 5 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers